The Effect of Corporate Governance on Financial Performance Mediated by Capital Structure - Fatmasari; Ana Mardiana (www.amertainstitute.com, 2023)
This study aims to analyze the effect of corporate governance on financial performance mediated by capitalstructure. The variables used in this study are corporate governance as an independent variable, financial performance as the dependent variable, and capital structure as a mediating variable. The basis used to explain between variables in this study comes from agency theory and trade-off theory. The population used is a manufacturing company listed on the Indonesia Stock Exchange (IDX) with a research period of 2018-2020. This study uses purposive sampling method in selecting samples and using secondary data. The number of companies that were sampled were 105 companies with a total of 88 data. The analytical method used is the path analysis method and the Sobel test for testing the mediation hypothesis. The results of this study indicate that managerial ownership has an insignificant negative effect on capital structure. The audit committee has a significant positive effect on the capital structure. Capital structure has a significant negative effect on financial performance. Managerial ownership has a significant positive effect on financial performance. The audit committee has no significant positive effect on financial performance. This study shows that the role of capital structure is not able to mediate the relationship between managerial ownership and financial performance. Finally, the role of capital structure is able to mediate the relationship between the audit committee on financial performance